PEMIKIRAN HUKUM KEWARISAN BILATERAL: STUDI PEMIKIRAN HAZAIRIN - Bakar, Abu (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2007)
The Sunni inheritance law divides the heirs into dzul faraid, ashabah,a nd dzl)l arham. while bilaterdl inherirance into dzul farajdh, dzul qarabat, and rnawali. The bilateml inheritance principles are; first, the female he;r is the same as the male hc;. in which thcy can obstrct the lower lllain heirg.oup, as long &s they still have children. son or daughier, then eirher the gmndfather or the brother or the sister can obslructed. Second, rhe male inheritance is as strong as the female one. Third, the subsiihrte heir (mawali) always inherirs, is never obstructd by other heirs. For example, a grandchild can inherit rogelher wiih the child when the parents pass away before the gandfitther, and ihe part that they receive is. as nucb as their pa.rents would receive (if still alive). The existence of mawali can reflect th faimess. Kalalal is a condition *hen a person passes away without leaving any descendent, that is anl direct descendent. either son or daughter.